2020
DOI: 10.1136/jim-2019-001119
|View full text |Cite
|
Sign up to set email alerts
|

Association between Coarse Particulate Matter (PM10-2.5) and Nasopharyngeal Carcinoma among Taiwanese Men

Abstract: The nasopharyngeal tract traps mainly coarse particles in inhaled air. Soluble carcinogenic compounds, endotoxins, and trace metals contained in these particles are potential causes of inflammation and oxidative stress which could enhance carcinogenesis. The aim of this study was to determine the association between coarse particulate matter (PM10-2.5) and nasopharyngeal cancer (NPC). A total of 521,098 men (355 cases and 520,743 non-cases), aged ≥40 years were included in this study. Data were retrieved from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Two studies that evaluated outdoor air pollution in Taiwan reported positive associations between ambient air levels of fine or coarse particulate matter and NPC risk (77,78), whereas a study of 10 Chinese cities found no significant association with fine and coarse particulate matter combined (79). In both settings, ambient air levels of nitrogen dioxide were associated with greater NPC risk (77,79).…”
Section: Tobacco and Other Smokementioning
confidence: 98%
“…Two studies that evaluated outdoor air pollution in Taiwan reported positive associations between ambient air levels of fine or coarse particulate matter and NPC risk (77,78), whereas a study of 10 Chinese cities found no significant association with fine and coarse particulate matter combined (79). In both settings, ambient air levels of nitrogen dioxide were associated with greater NPC risk (77,79).…”
Section: Tobacco and Other Smokementioning
confidence: 98%
“…In the cell viability test, we found that RA-RF (0-800 µg/mL) and PMFF (0-200 µg/mL) had no effect on cytotoxicity, but the high concentrations of PMFF (400 and 800 µg/mL) significantly decreased cell survival. The cytotoxic effects of PMFF may depend on the concentration of PAHs, metals, endotoxins, and other elements [57,58]. Interestingly, co-treated PMFF with RA-RF had no effect on cell apoptosis and necrosis.…”
Section: Discussionmentioning
confidence: 97%
“…The health effects of human inhalation exposure to PMFF containing PAHs from fire haze could induce oxidative stress, inflammation, invasion, migration, and risk of lung cancer [13,[54][55][56]. Furthermore, these harmful effects might be also caused by metals, endotoxins, and other elements in PMFF [57,58] In this investigation, PAH content in PMFF, cytotoxicity, ROS, pro-inflammatory cytokines, invasion and migration effects, and the molecular mechanism of RA-RF on A549 cells induced by PMFF were determined. In the cell viability test, we found that RA-RF (0-800 µg/mL) and PMFF (0-200 µg/mL) had no effect on cytotoxicity, but the high concentrations of PMFF (400 and 800 µg/mL) significantly decreased cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous cohort studies of PM have focused on lung cancer [ 3 ]. Although the mutagenic, epigenetic, and inflammatory mechanisms are shared largely with all types of cancer, it is only recently that large cohort studies have begun to expand to other cancer types [ 27 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Furthermore, there have only been a few studies that compared the associations across different types of cancer and identified the specific sites more affected by PM air pollution than others.…”
Section: Discussionmentioning
confidence: 99%